2020
DOI: 10.4142/jvs.2020.21.e61
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofPanax notoginsengsaponins on oxidative stress induced by PCV2 infection in immune cells:in vitroandin vivostudies

Abstract: Background: Panax notoginseng saponins (PNS) are bioactive substances extracted from P. notoginseng that are widely used to treat cardiovascular and cerebrovascular diseases and interstitial diseases. PNS have the functions of scavenging free radicals, anti-inflammation, improving blood supply for tissue and so on. Objectives: The aim of this study was to investigate the effects of PNS on the oxidative stress of immune cells induced by porcine circovirus 2 (PCV2) infection in vitro and in vivo. Methods: Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…17 Treatment of porcine circovirus 2-infected porcine lung cells with PNS resulted in a significant reduction in intracellular NO content and xanthine oxidase activity, which suggested that PNS could regulate the oxidative stress of immune cells. 18 PNS decreased serum MDA, lactate dehydrogenase, myocardial tissue superoxide dismutase, and reactive oxygen species. 19 Ginsenoside Rg1, a natural compound isolated from PNS, promoted HUVEC progression into the S and G2/M phases of the cell cycle and markedly elevated EGFR secretion and had a notable effect on HUVEC migration and tube formation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…17 Treatment of porcine circovirus 2-infected porcine lung cells with PNS resulted in a significant reduction in intracellular NO content and xanthine oxidase activity, which suggested that PNS could regulate the oxidative stress of immune cells. 18 PNS decreased serum MDA, lactate dehydrogenase, myocardial tissue superoxide dismutase, and reactive oxygen species. 19 Ginsenoside Rg1, a natural compound isolated from PNS, promoted HUVEC progression into the S and G2/M phases of the cell cycle and markedly elevated EGFR secretion and had a notable effect on HUVEC migration and tube formation.…”
Section: Discussionmentioning
confidence: 88%
“…Dammarane‐type triterpenoid saponins could inhibit NO activities in a dose‐dependent manner 17 . Treatment of porcine circovirus 2‐infected porcine lung cells with PNS resulted in a significant reduction in intracellular NO content and xanthine oxidase activity, which suggested that PNS could regulate the oxidative stress of immune cells 18 . PNS decreased serum MDA, lactate dehydrogenase, myocardial tissue superoxide dismutase, and reactive oxygen species 19 .…”
Section: Discussionmentioning
confidence: 99%
“…PNS can promote the proliferation of hematopoietic progenitor cells and modulate T cell immune functions ( 19 ). PNS can inhibit the oxidative stress of immune cells when infected with PCV2 ( 20 ). At present, research on the anti-viral activity of PNS is still in its infancy, and its immunomodulatory effects have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…e Huangjia Ruangan granule is a pure Chinese medicine compound preparation, which is composed of Hedysarum Multijugum Maxim (Huangqi, HQ), Trionyx sinensis Wiegmann (Biejia, BJ), Radix Puerariae (Gegen, GG), Radix Bupleuri (Chaihu, CH), Ganoderma (Lingzhi, LZ), Radix Paeoniae Rubra (Chishao, CS), Radix Salviae (Danshen, DS), Panax Notoginseng (Sanqi, SQ), Abri Herba (Jigucao, JGC), and Phyllanthus urinaria L (YeXiaZhu, YXZ). HQ and CH are used to ameliorate liver injury [14,15]; BJ can soften and disperse knots; LZ, CS, DS, and SQ can promote the blood circulation and have antioxidant and anti-inflammatory effects [16][17][18][19]; GG, JGC, and YXZ can detoxify damp-heat residual toxins [5,20,21]. e combination of these drugs exerts a variety of pharmacological effects, such as antioxidation, anti-inflammatory, and antifibrosis while protecting the liver and relieving depression.…”
Section: Introductionmentioning
confidence: 99%